Multifaulting in a tectonic syntaxis revealed by InSAR: The case of the Ziarat earthquake sequence (Pakistan). Issue 7 (1st July 2014) - Pinel‐Puysségur, B.; Grandin, R.; Bollinger, L.; Baudry, C.
Abstract On 28–29 October 2008, within 12 h, two similar Mw = 6.4 strike‐slip earthquakes struck Baluchistan (Pakistan), as part of a complex seismic sequence. Interferometric Synthetic Aperture Radar (InSAR) data reveal that the peak of surface displacement is near the Ziarat anticline, a large active fold affected by Quaternary strike‐slip faulting. All coseismic interferograms integrate the deformation due to both earthquakes. As their causative faults ruptured close to each other, the individual signals cannot be separated. According to their focal mechanisms, each earthquake may have activated a NE‐SW sinistral or a NW‐SE dextral fault segment, which leads to four possible scenarios of fault orientations. A nonlinear inversion of the InSAR data set allows rejecting two scenarios. The best slip distributions on the two fault segments for the two remaining scenarios are determined by linear inversion. Stress‐change modeling favors a scenario involving two abutting conjugate strike‐slip faults. Two other fault segments accommodated left‐lateral strike slip during the seismic sequence. The activated fault system includes multiple fault segments with different orientations and little surface expression. This may highlight, at a smaller scale, the distributed, possibly transient character of deformation within a broader right‐lateral shear zone. It suggests that the activated faults delineate a small tectonic block extruding and subtly rotating within the shear zone. It occurs in the vicinity of the local tectonic syntaxis where orogenic structures sharply turn around a vertical axis. These mechanisms could participate in the long‐term migration of active tectonic structures within this kinematically unstable tectonic syntaxis.